Marketing Strategical Analysis of Products UMKM Markets with Tol - Muhammad Iqbal Nasution; Muhammad Syukri Albani Nasution; Nur Ahmadi Bi Rahmani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Marketing Strategy is a way for UMKM players to introduce their products to the wider community in order to achieve the desired vision and mission. The aim of this research is to find out what marketing strategies business actors use to maintain income stability in accordance with the 4Ps. This research is descriptive qualitative research. The data collection methods used in this research are interviews and observation. The results of this research show that 1) Every UMKM actor in the workshop market, if they want to be better known for their products, they can use methods such as the program carried out by the Industry and Trade Department, where they take advantage of festivals or other important celebrations to advance regional businesses. and it was proven that they could reap profits from the event from selling food alone which was around ± Rp. 3,000,000 million in two days. 2). UMKM players can also rearrange the composition of the materials usually used or pay attention to the quality of the raw materials so that the product results are better than before.